A Case of Ruptured Aortic Arch Aneurysm Successfully Treated by Thoracic Endovascular Aneurysm Repair with Chimney Graft. (28th February 2015) - Kawatani, Yohei; Hayashi, Yujiro; Ito, Yujiro; Kurobe, Hirotsugu; Nakamura, Yoshitsugu; Suda, Yuji; Hori, Takaki
Abstract : We report the case of aortic arch aneurysm rupture treated successfully with thoracic endovascular aneurysm repair (TEVAR) accompanied by aortic arch debranching using the chimney graft technique. A 94-year-old man was transported to the hospital after complaining of chest pain for one day. Contrast-enhanced computed tomographic (CT) images revealed an aortic arch aneurysm rupture. Considering the patient's age and postoperative activities of daily living, TEVAR was used. In order to place an indwelling stent graft from the ascending aorta to the periphery, the chimney graft technique was used to debranch the brachiocephalic artery. Hemodynamics was stabilized postsurgically. Plain CT performed 20 days postoperatively confirmed that the intrathoracic hematoma had decreased in size. Although respiratory failure was persistent, there were improvements and the patient was extubated 34 days postoperatively and discharged from the intensive care unit 37 days postoperatively. On postoperative day 75, he was discharged from the hospital to an elder care facility. Few reports have focused on stent grafting for treating aortic arch aneurysm rupture. TEVAR using the chimney graft technique could be an effective treatment option for patients with a decreased ability to tolerate surgery.